Innovative Structural Design of a Warren Truss Steel Bridge Utilizing Double Angle Sections - Kuncoro, Hendrian Budi Bagus; Sari, Rizki Yunita (JURUSAN TEKNIK SIPIL, 2026)
Warren truss-type steel bridges are a popular choice for short- to medium-span applications due to their structural efficiency and straightforward fabrication. Despite these advantages, further optimization of structural elements remains essential to improve performance and reduce costs. This study focuses on the structural design and analysis of an 8-meter Warren truss steel bridge using double angle profiles (50 × 50 × 5 mm) to enhance strength and material efficiency. The bridge was modeled and analyzed using SAP2000 software, considering various load combinations—dead, live, wind, and ultimate—according to the SNI 1725:2016 and SNI 1729:2015 standards. Structural verification involved evaluating axial forces in truss members, the capacity of A325 Ø10 mm bolted connections, and overall stability. The results demonstrated that all structural components operated within safe limits, with strength ratios below 0.95 and a maximum vertical deflection of 0.00416 mm, well under the allowable deflection threshold (1/800 L). The total weight of the bridge frame was 607.94 kg. These findings indicate that the use of double angle profiles in Warren truss bridges offers a structurally sound and cost-effective solution suitable for short- to medium-span bridge construction in Indonesia.